EXPERIMENTAL STUDY ON THERMAL STRESS OF FASTENED HYBRID COMPOSITE/METALLIC STRUCTURES UNDER DIFFERENT TEMPERATURES - CAO Su; LEI Kai; CHEN XiangMing; WEI JingChao; CHENG LiNan (Jixie qiangdu)
Extreme climatic conditions,such as hot,cold and hot-humid environment,affect the bearing performance and the life expectancy of composite and metal hybrid structural components in aircraft,which have a great impact on the flight performance and safety of the aircraft.Due to the large coefficient of thermal expansion mismatch between the composite and metallic structures,the temperature change in the actual flight condition induces high thermal stresses in both composite component and metallic component.This additional stress would alter load transfer and internal stress distribution in fastened hybrids of composite and metallic structure.Thermal/mechanical behavior of the large-scale,multi-joint hybrid composite/metal structure was investigated experimentally in different temperature conditions,as well as bearing axial load under different temperatures.The internal stress distribution of different components and fasteners in hybrid composite/metal structure under different temperature and load conditions was obtained by the strain gage method.